ANALISIS PEMBELAJARAN TEMATIK MASA PANDEMI COVID-19 PADA PESERTA DIDIK SD NEGERI 37 PONTIANAK TENGGARA - Ema Wahyuni; Tahmid Sabri; Kartono Kartono (Universitas Tanjungpura, 2022)
AbstractThis studi aims to describe the process of ilmpementing thematic learning during the Covid-19 pandemic, as well as the supporting and inhibiting factors for thematic learning during the Covid-19 pandemic. This research is included in the descriptive type of qualitative research. The data collection techniques in this study used interviews, observation, and documentation. The qualitative data analysis technique used is the Miles and Hubermen interactive model. To test the credibility of the data one the results of the study using technical triangulation and soure triangulation. The results of the analysis show that the process of implementing thematic learning during the Covid-19 pandemic was carried out by online and offline distance learning for class IV and class II students using the WhattsApp application as the main medium in communicating and providing materials and school assignments.Supporting factors during thematic learning during the Covid-19 pandemic, namely, the exixtence of adequate facilities and infrastructure, the use of learning media, as well as support from parents, as for the inhibiting factors for thematic learning during the Covid-19 pandemic, namely, limited facilities and infrastructure owned by students, difficulties in using learning media, lack of understanding of students on learning materials, parents who are busy working, and discipline of students/parents.Keyword : Analysis, Covid-19 Pandemic, Thematic Learning